Existence of lipid vesicles containing platelet-activating factor in endothelial cell lysate. Issue 1 (February 1992) - Kojima, S.; Nara, K.; Inada, Y.; Hirose, S.; Saito, Y.
Abstract : Platelet aggregation activity due to platelet-activating factor (PAF) was detected at high molecular weight (HMW) and low molecular weight fractions after gel-filtration chromatography of cell lysate of endothelial cells. [ 3 H]PAF added to the cell lysate was similarly distributed after chromatography. The radioactivity associated with HMW fraction was not reduced by digesting the lysate with trypsin, suggesting that PAF was not making complexes with proteins but was included in lipid vesicles in cell lysate. Further evidence showed that an unknown specific factor(s) was needed to form these PAF-containing lipid vesicles. Radioactivity was not found in HMW fraction when [ 3 H]PAF was mixed with cell lysate of vascular smooth muscle cells. When monomeric PAF was added to endothelial cell lysate, the specific activity of aggregation decreased to the level exerted by endogenous PAF-containing lipid vesicles due to incorporation into lipid vesicles. PAF in the form of lipid vesicles was more stable in plasma than monomeric form.